ESTETIKA MOTIF BATIK TULIS DI IDA BATIK BONDOWOSO - Putri Ana Sabilillah; Luh Suartini; I Nyoman Rediasa (Universitas Pendidikan Ganesha, 2026)
This research is a research on the aesthetic analysis of batik tulis motifs at Ida Batik Bondowoso with the aim of increasing public appreciation of batik tulis. Ida Batik Bondowoso is located in Kalianyar Village, Tamanan District, Bondowoso Regency, East Java. This research describes the tools, materials, batik making process, various batik motifs, and describes the aesthetics of each motif in batik tulis at Ida Batik Bondowoso. This research uses a descriptive qualitative approach with data collection techniques of observation, interviews, documentation, and literature. The results of the data obtained from various sources are analyzed using domain analysis and taxonomic analysis using the theory of the process of making batik tulis, batik tulis motifs, and aesthetics. The results of this research are (1) the tools and materials used are tablets, printers, pencils, canting, frying pans, electric stoves, sponge brushes, tracing paper, katuan primissima cloth, malam (wax), remasol dye, waterglass. The process of making hand-drawn batik begins with making a pattern design, printing the pattern, transferring the pattern to the cloth, using a canting, coloring, applying water glass to the cloth, rolling, boiling the cloth to remove the wax on the cloth and ends with drying the cloth. (2) The various hand-drawn batik motifs of Ida Batik Bondowoso are cassava leaves, coffee leaves, coffee, roof tiles, tofu, tobacco leaves, Ijen geopark, birds of paradise, and birds of paradise. (3) Aesthetic analysis of hand-drawn batik motifs at Ida Batik Bondowoso shows that each hand-drawn batik motif is combined into one design created from various aesthetic elements such as dots, lines, planes, and colors which are applied through the principles of fine art of unity, balance, rhythm, emphasis, proportion, and harmony so that a design with high aesthetic value can be created. Keywords: aesthetic, batik tulis, ida batik Bondowoso.